Ecological Economic Transformation in 3T Areas: The Role and Improvement of the BAZNAS Program - Rifqah Najwa Azizah; Andhika Tiara; Taufik Illahi; Sihabussalam Sihabussalam (International Journal of Zakat, 2025)
This paper discusses the potential of 3T (Disadvantaged, Outermost, and Frontier) regions and the role of BAZNAS in improving ecological economy programs. This study observes the importance of harmonization between economic development and environmental conservation as a form of ecological economic transformation. Through a descriptive-exploratory qualitative method, this paper shows that the 3T area has sea, forest, and agricultural potential that needs to be mapped first by BAZNAS efficiently and collaboratively so that it has ecological economic value. BAZNAS can play a role with three main programs: first, ecological sustainability, which has the main goal of protecting the environment but still producing something of economic value. Second, environmental productive zakat, which maximizes the results of zakat not only in providing capital and training, but is directed to the circular economy. Third, the blue BAZNAS program focuses on empowering coastal communities for marine products and preventing pollution of marine ecosystems. This research contributes to transforming the BAZNAS program in the economic sector, optimizing the natural potential of the 3T area through resource mapping, and the implementation of three ecological economy programs that can realize community welfare while maintaining environmental sustainability.